SOCIAL FACTORS AFFECTING OBSOLESCENCE. - Moyer, C. A. (The Accounting Review, 1943)
Abstract War conditions as in 1917 and 1918; have again focused considerable attention upon obsolescence. Most of this attention is directed to obsolescence as it affects income taxes. In 1918 the Bureau of Internal Revenue first permitted the accruing of ordinary or normal obsolescence through the depreciation rate. During the present conflict the granting of war-necessity certificates and the use of accelerated depreciation rates result in part from the recognition of the desirability of accruing obsolescence, even though such accrual is merged with physical depreciation. Conversion of facilities to the manufacture of war supplies, and other changes which have been required in manufacturing processes forcibly bring to the attention of accountants and owners certain factors which are present in a lesser degree at all times. If a product or service is no longer in demand, then producers are forced to abandon equipment at once. This condition would cause compulsory obsolescence. However, in the case of improvements or the appearance of new techniques in production, a producer may often exercise the choice of using the old equipment for a longer period of time or of substituting the new equipment at once.